Pembangunan Sistem Rekrutmen Kampus Studi Kasus Unit Pengembangan Karir dan Kewirausahaan Universitas Brawijaya - Nurhaida Syadrina; Denny Sagita Rusdianto; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
University of Brawijaya's career development and entrepreneurship unit (UPKK UB) has service facilities provided to UB alumni and other university students. On the implementation, there is a problem in limited amount of the job vacancy information provided by UPKK UB and it is not enough to fill needs of people who use the services of UPKK UB in finding job vacancies. Also, there are problems in the process of campus recruitment which slow down the staff duties in conducting the campus recruitment process. To solve the problem of UPKK UB services, the campus recruitment system is developed, so that the service provided by UPKK UB can run well. In the development of campus recruitment system, there are 78 functional requirements and 2 non-functional requirements, the system is developed using waterfall system development life cycle. The result of unit test, integration, and validation are 100%, and the result of compatibility are 82%, and performance efficiency in time behavior tests are 0.196 seconds, with resource utilization which are RAM Â± 2.337 MB and CPU Â± 0.31%, capacity is 146 users.